Molecular cytogenetic characterization of Dasypyrum breviaristatum chromosomes in wheat background revealing the genomic divergence between Dasypyrum species - Li, Guangrong (Mol Cytogenet, 2016)
BACKGROUND: The uncultivated species Dasypyrum breviaristatum carries novel diseases resistance and agronomically important genes of potential use for wheat improvement. The development of new wheat-D. breviaristatum derivatives lines with disease resistance provides an opportunity for the identification and localization of resistance genes on specific Dasypyrum chromosomes. The comparison of wheat-D. breviaristatum derivatives to the wheat-D. villosum derivatives enables to reveal the genomic divergence between D. breviaristatum and D. villosum. RESULTS: The mitotic metaphase of the wheat- D. breviaristatum partial amphiploid TDH-2 and durum wheat -D. villosum amphiploid TDV-1 were studied using multicolor fluorescent in situ hybridization (FISH). We found that the distribution of FISH signals of telomeric, subtelomeric and centromeric regions on the D. breviaristatum chromosomes was different from those of D. villosum chromosomes by the probes of Oligo-pSc119.2, Oligo-pTa535, Oligo-(GAA)(7) and Oligo-pHv62-1. A wheat line D2139, selected from a cross between wheat lines MY11 and TDH-2, was characterized by FISH and PCR-based molecular markers. FISH analysis demonstrated that D2139 contained 44 chromosomes including a pair of D. breviaristatum chromosomes which had originated from the partial amphiploid TDH-2. Molecular markers confirmed that the introduced D. breviaristatum chromosomes belonged to homoeologous group 7, indicating that D2139 was a 7V(b) disomic addition line. The D2139 displayed high resistance to wheat stripe rust races at adult stage plant, which may be inherited from, D. breviaristatum chromosome 7V(b). CONCLUSION: The study present here revealed that the large divergence between D. breviaristatum and D. villosum with respected to the organization of different repetitive sequences. The identified wheat- D. breviaristatum chromosome addition line D2139 will be used to produce agronomically desirable germplasm for wheat breeding.